Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(3x^2-3xy-5x+5y=3x\left(x-y\right)-5\left(x-y\right)=\left(3x-5\right)\left(x-y\right)\\ x^3-3x^2-4x+12=x^2\left(x-3\right)-4\left(x-3\right)=\left(x-2\right)\left(x+2\right)\left(x-3\right)\\ 45+x^3-5x^2-9x=x^2\left(x-5\right)-9\left(x-5\right)=\left(x-3\right)\left(x+3\right)\left(x-5\right)\)
a) \(x^3y^3+125=\left(xy\right)^3+5^3=\left(xy+5\right)\left(x^2y^2-5xy+25\right)\)
b) \(8x^3+y^3-6xy\left(2x+y\right)=\left(8x^3+y^3\right)-6xy\left(2x+y\right)=[\left(2x\right)^3+y^3]-6xy\left(2x+y\right)\)
\(=\left(2x+y\right)\left(4x^2-2xy+y^2\right)-6xy\left(2x+y\right)=\left(2x+y\right)\left(4x^2-2xy+y^2-6xy\right)\)
\(=\left(2x+y\right)\left(4x^2-8xy+y^2\right)\)
c) \(\left(3x+2\right)^2-2\left(x-1\right)\left(3x+2\right)+\left(x-1\right)^2\)
\(=[\left(3x+2\right)-\left(x-1\right)]^2=\left(3x+2-x+1\right)^2=\left(2x+3\right)^2=\left(2x+3\right)\left(2x+3\right)\)
b. 2x3-3x2+3x-1=2x3-x2-2x2+x+2x-1
= x2(2x-1)-x(2x-1)+(2x-1)
=(2x-1)(x2-x-1)
c. 3x3-14x2+4x+3= 3x3+x2-15x2-5x+9x+3
=x2(3x+1)-5x(3x-1)+3(3x+1)
=(3x+1)(x2-5x+3)
Phân tích đa thức thành nhân tử(tách hạng tử)
1)x^2+2x-3=x^2-x+3x-3=x(x-1)+3(x-1)=(x-1)(x+3)
2)x^2-5x+6=x^2-2x-3x+6=x(x-2)-3(x-2)=(x-2)(x-3)
3)x^2+7x+12=(x+3)(x+4)
4)x^2-x-12=(x-4)(x+3)
5)3x^2+3x-36=3[(x-3)(x+4)]
6)5x^2-5x-10=5[(x-2)(x+1) ]
7)3x^2-7x-6=(x-3)(3x+2)
8)4x^2+4x-3=4x^2+6x-2x-3=(2x-1)(2x+3)
9)8x^2-2x-3=8x^2+4x-6x-3=(4x-3)(2x+1)
1: \(x^2+2x-3=\left(x+3\right)\left(x-1\right)\)
2: \(x^2-5x+6=\left(x-2\right)\left(x-3\right)\)
3: \(x^2+7x^2+12x=4x\left(2x+3\right)\)
4: \(x^2-x-12=\left(x-4\right)\left(x+3\right)\)
5: \(3x^2+3x-36=3\left(x^2+x-12\right)=3\left(x+4\right)\left(x-3\right)\)
6: \(5x^2-5x-10=5\left(x^2-x-2\right)=5\left(x-2\right)\left(x+1\right)\)
1: \(\dfrac{A}{B}=\dfrac{2x^4+4x^3-x^3-2x^2-2x^2-4x+x+2}{x+2}\)
\(=2x^3-x^2-2x+1\)
6, (x^2 +1) -4x^2 = x^2 + 1 - 4x^2 = 1 - (4x^2 - x^2) = 1 - 3x^2 = (1-\(\sqrt{3}\)x)(1+\(\sqrt{3}\)x)
7, x^2 - 4x -5 = x^2 - 2.x.2 + 4 - 9 = (x^2 - 2.x.2 +4) - 3^2 = (x-2)^2 - 3^2 = (x-2-3)(x-2+3) = (x-5)(x+1)
8, x^5 - 3x^4 + 3x^3 - x^2 = x^2(x^3 -3x^2 + 3x -1) = x^2(x-1)^3